Transaction Processing System for Incoming and Outgoing Goods at BUMDes Kamulyan Store, Tasikmalaya Regency - Novia Nurul Hidayah; Didin Syahidin (Journal of Applied Information System and Informatic (JAISI), 2026)
BUMDes Kamulyan Store is a village-owned enterprise unit that plays a role in fulfilling community needs while supporting local economic growth. To ensure orderly and efficient operations, a system for recording incoming and outgoing goods transactions is required. This study aims to produce a proposed information system design to facilitate and streamline the data processing of goods transactions at BUMDes Kamulyan Store. The research employs a descriptive method. The system is developed using the Prototype method, supported by analytical tools such as Flowmaps, Context Diagrams, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD). The system design is implemented using Microsoft Visual Studio 2008 with the C# (C-Sharp) programming language, and Microsoft Office Access as the database design tool. The results of the study indicate that the recording of goods transactions at BUMDes Kamulyan Store, Tasikmalaya Regency, is still conducted manually using transaction books. The proposed information system, developed using Microsoft Visual Studio and the C# programming language, has proven to facilitate and improve the process of recording and reporting incoming and outgoing goods transactions more quickly and accurately.